Bandwidth Management using Per Connection Queue and Queue Tree: A Case Study on a High School Network - Prasetyo, Eko; Santoso, Tossy; Riyadi, Slamet; ., Asroni (Universitas Muhammadiyah Yogyakarta, 2024)
This research aims to enhance the efficiency of bandwidth utilization at MTs Muhammadiyah Tawangsari using the PCQ and Queue Tree bandwidth management methods on a MikroTik router. Through this approach, an analysis of bandwidth requirements, network topology design, and implementation were conducted. Post-implementation measurement results show a remarkable improvement in average user download speeds: 17.3 Mbps in administration rooms, 10 Mbps in classrooms, and 18.8 Mbps in faculty rooms. These results indicate a significant improvement in tailored bandwidth distribution that meets the specific needs of each network area and ensures that all users receive equal bandwidth usage. This leads to more evenly distributed and efficient network performance.